Association of aortic arch and aortic valve calcifications with cardiovascular risk in patients on maintenance hemodialysis - Liao, Min-Tser; Chao, Chia-Ter; Wu, Chung-Kuan (Frontiers in Cardiovascular Medicine, 2022)
Introduction: This study aimed to investigate the association of aortic arch calcification (AoAC) and aortic valve calcification (AVC) with major adverse cardiovascular events (MACE) and cardiovascular and all-cause mortality in patients on maintenance hemodialysis (MHD). Methods: This study enrolled 297 adult patients with end-stage kidney disease who were on MHD. They were divided into those with an AoAC score <2 without AVC (n=70, 23.6%), those with an AoAC score <2 with AVC (n=96, 32.3%), and those with an AoAC score ≥2 regardless of AVC status (n=131, 44.1%). We analyzed the risks of MACE, cardiovascular and overall mortality among the three groups using Cox proportional hazard analyses. Survival probabilities were estimated using the log-rank test via the Kaplan–Meier method. Results: Kaplan–Meier analysis revealed that the MACE-free rate and the survival rates of cardiovascular and overall mortality were significantly higher in adult chronic hemodialysis patients with AoAC score <2 without AVC, followed by those with AoAC score <2 with AVC, and then those with AoAC score ≥2 (log-rank test; all p<0.01). The grade of AoAC is a significant risk factor for MACE, cardiovascular mortality, and overall mortality after adjusting for age and gender Relative to AoAC score <2 without AVC, adult chronic hemodialysis patients with AoAC score ≥2 remained an independently significantly risk factor of MACE (adjusted hazard ratio, 2.17; 95% confidence interval 1.11 to 4.20; p=0.023) after adjusting for age, sex, and all significant variables in baseline characteristics. Conclusions: AoAC grade was positively correlated with a higher risk of MACE and cardiovascular and overall mortality. Furthermore, the presence of AVC modified the adverse cardiovascular risk associated with AoAC in patients on MHD.